CONSTRUCTION AND VALIDATION OF AN EDUCATIONAL VIDEO FOR NURSES ON THE MANAGEMENT OF NEUROPATHIC ULCER ASSOCIATED WITH LEPROSY - Souza, Camilla Borges Lopes; Brandão, Maria Girlane Sousa Albuquerque; Silva, Policardo Gonçalves da; Borges, Amanda Aparecida; Terçariol, César Augusto Sangaletti; Nogueira, Paula Cristina; Rabeh, Soraia Assad Nasbine (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objectives: To build and validate an educational video for nurses on the management of neuropathic ulcers. Method: Methodological study carried out in four stages: script/storyboard production; content and face validation of the script/storyboard with judges in a virtual environment judges in July 2018; video editing; and semantic validation with representatives of the target audience. The video script was validated by nine specialists in the subject and eight technical judges. For semantic validation, a focus group was used with nine nurses, in August 2018, in an outpatient clinic of a higher education institution in Minas Gerais, Brazil. Results: The video was entitled “Evaluation for the management of neuropathic ulcer associated with leprosy” and lasted 18 minutes and 32 seconds. For all questions, a content validity index of more than 78% was obtained, in a single round. The suggestions issued by the judges promoted changes in the scenes, with the inclusion of images, photos, and more accessible language. Conclusion: The video was considered valid by judges and the target audience and may contribute to nurses’ updating on the subject, with positive effects on care for people with leprosy.